The changing role of history in restoration ecology. Issue 9 (1st November 2014) - Higgs, Eric; Falk, Donald A; Guerrini, Anita; Hall, Marcus; Harris, Jim; Hobbs, Richard J; Jackson, Stephen T; Rhemtulla, Jeanine M; Throop, William
Abstract : In the face of rapid environmental and cultural change, orthodox concepts in restoration ecology such as historical fidelity are being challenged. Here we re‐examine the diverse roles played by historical knowledge in restoration, and argue that these roles remain vitally important. As such, historical knowledge will be critical in shaping restoration ecology in the future. Perhaps the most crucial role in shifting from the present version of restoration ecology ("v1.0") to a newer formulation ("v2.0") is the value of historical knowledge in guiding scientific interpretation, recognizing key ecological legacies, and influencing the choices available to practitioners of ecosystem intervention under conditions of open‐ended and rapid change.